Highlighting of the interactions of MYD88 and NFKB1 SNPs in rats resistant to decompression sickness: toward an autoimmune response - Vallée, Nicolas; Dugrenot, Emmanuel; Desruelle, Anne-Virginie; Richard, Simone; Coupé, Stéphane; Ramdani, Céline; Guieu, Régis; Risso, Jean-Jacques; Gaillard, Sandrine; Guerrero, François (Frontiers in Physiology, 2023)
Decompression sickness (DCS) with neurological disorders includes an inappropriate inflammatory response which degenerates slowly, even after the disappearance of the bubbles. There is high inter-individual variability in terms of occurrence of DCS that could have been mastered by the selection and then the breeding of DCS-resistant rats. We hypothesized the selection of SNPs linked to auto-immunity operated upon generation of DCS-resistant strain of rats. We used the candidate gene approach and targeted SNPs linked to the signaling cascade that directly regulates inflammation of innate immunity transiting by the Toll like receptors. Twenty candidate SNPs were investigated in 36 standard rats and 33 DCS-resistant rats. For the first time, we identify a diplotype (i.e. with matched haplotypes)when coinheritedstrengthen protection against DCS, which is not strictly homozygous and that suggests that a certain tolerance may be considered. We deduced from it an ideal haplotype of 6 variants (MyD88_50-T, _49-A, _97-C coupled to NFKB_85-T, _69-T, _45-T) linked to the resistant phenotype. Four among the six identified variants are located in pre-and/or post-transcriptional areas regulating MyD88 or NFKB1 expression. Because of missenses, the other 2 variants induce in the NFKB1 protein complex a structural change including one damage according to the missense3D algorithm. In addition to this MyD88/NFKB1 haplotype which gives rats a strong resistance to DCS, this again highlights the importance that the immune response, here linked to the genetic heritage, can have in the development of DCS and offer a new perspective for therapeutic strategy.